Pathophysiological basis of low contrast visual acuity loss in multiple sclerosis. Issue 12 (24th October 2018) - Triplett, James D.; Yiannikas, Con; Barnett, Michael H.; Parratt, John; Barton, Joshua; Graham, Stuart L.; You, Yuyi; Klistorner, Alexander
Abstract: Objective: There is currently an urgent need for reliable clinical biomarkers of remyelination to be used in Phase 2 and Phase 3 clinical trials. Low contrast visual acuity (LCVA) has been suggested as a functional measure of the integrity of the visual pathway. Therefore, the aim of this study was to elucidate the potential contribution of axonal loss and demyelination to LCVA loss in MS patients. Method: In this study, 50 consecutive relapsing remitting MS patients with a previous history of unilateral optic neuritis were enrolled. Using the linear regression model, we assessed the relative contribution of multifocal Visual Evoked Potentials (mfVEP) latency and Retinal Nerve Fiber Layer (RNFL) thickness to LCVA deficit. Results: Intereye asymmetry of mfVEP latency and RNFL thickness correlated significantly with intereye asymmetry of LCVA ( P  < 0.001). A linear regression model demonstrated increased predictive power of LCVA when mfVEP latency and RNFL thinning were combined (reaching R 2  = 0.67) and confirmed a higher predictive value of RNFL thinning compared to mfVEP latency delay for both contrast levels. However, elimination of subjects with severe axonal loss dramatically increased the relative contribution of mfVEP latency, with contribution of RNFL thickness losing significance for both 1.25% and 2.5% LCVA. Interpretation: While retinal ganglion cell axonal loss is a superior predictor of LCVA, the degree of demyelination contributes significantly to worsening of LCVA, particularly when patients with severe axonal loss are excluded. These results support the feasibility of using LCVA as a functional biomarker in remyelination therapy trials, providing appropriate patient's selection criteria are implemented.